EFEK IMPRESI COVID 19 SERTA KESIAPAN TEKNOLOGI INFORMASI UMKM OLE-OLE KHAS MALUKU - Micrets Agustina Silaya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to provide an overview of the impact of covid 19 and technologicalreadiness by Micro, Small and Medium Enterprises typical Maluku souvenirs in the cityof Ambon. The research was conducted on 42 typical Moluccan ole-ole businesses inAmbon City. 13 of them are shops that sell all typical Moluccan ole-ole products, theremaining 29 are ole-ole shops with shell decorations. The results of the study found thatin general the readiness of information technology (IT) by MSMEs was at a low level.Many factors hinder IT readiness, such as human resources, technology resources andlack of working capital. SMEs that use IT are still at the operational or opportunisticlevel, and have not yet reached the strategic level. Moreover, in this condition, this paperalso provides several recommendations to improve IT readiness by MSMEs with policyinterventions and the implementation of several programs.